Revisão Sistemática e Metanálise da Eficácia da Pesquisa de Corpo Inteiro pré-dose terapêutica com 131I em indivíduos com Carcinoma Diferenciado da Tireoide - Petrocelli, Diego [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Although being controversial, some services use Whole Body Imaging (WBI) with 131I prior to the ablative dose with this radiopharmaceutical in the treatment of differentiated thyroid cancers (DTC). Proponents of this approach argue for a better optimization of the ablative dose, and opponents argue that this WBI could lead to the "stunning effect" characterized by reduced tissue uptake of 131I in ablative dose treatment, thereby compromising treatment and prognosis of these individuals. Objective: To evaluate whether WBI with 131I, ablative pre-dose, interferes with the efficacy of the therapeutic dose of iodine as remission of the disease after total or near total thyroidectomy in individuals with DTC. Methodology: A systematic review of the literature was conducted in which randomized, non-randomized and observational studies were included in which the patients were in the late postoperative period of total or subtotal thyroidectomy due to one of the DCT and were assigned the diagnostic WBI with I131 before the ablative dose (intervention) or they performed WBI with 123I before the ablative dose, or non-performance of the diagnostic WBI (directly ablative dose with 131I) (control). The primary outcome was disease remission assessed by the ablative success rate at least six months after follow-up. Results: After performing the searches in the following electronic databases Embase (1980-25/04/2017), Pubmed (1966-25/04/2017), CENTRAL (Cochrane Controlled Trials Register) (04/25/2017) and Virtual Health Library (1982-25 /04/2017), we identified 3005 references. Two reviewers independently assessed the titles and abstracts identified by the literature search, and of these, 23 were potentially eligible, and they were selected for reading in full. Twelve studies were included: four are prospective and eight retrospective. In the four prospective studies, the ablative success rate at six months was 86% in the intervention group and 87% in the control, the meta-analysis showed no significant difference between the groups (RR 1.02, CI 0.92,1.13, p = 0.66, I2 = 0%). Among the observational studies, four studies did not present significant differences between the groups, and in three the control group had a significantly higher ablative success rate. Conclusion: With a low quality of evidence, among the prospective studies there was no significant difference in the ablative success rate in patients who underwent pre-dose PCI with 131I or performed it with 123I or did not have this diagnostic PCI. Among observational studies, in three studies, individuals who performed pre-dose PCI with 131I had a significant reduction in ablative success rate at six months of follow-up, whereas in four studies there was no significant difference between groups.

Apesar de existirem controvérsias, alguns serviços utilizam a pesquisa de corpo inteiro (PCI) com 131I previamente a dose terapêutica com esse radionuclídeo no tratamento dos cânceres diferenciados da tiroide (CDT). Os defensores dessa conduta argumentam uma melhor otimização da dose ablativa, e os contrários afirmam que essa PCI poderia ocasionar o “efeito stunning”, caracterizado pela redução da captação tecidual do 131I no tratamento com a dose ablativa, comprometendo com isso o tratamento e o prognóstico desses indivíduos. Objetivo: avaliar se a PCI com 131I, pré-dose ablativa, interfere na eficácia da dose terapêutica de iodo quanto a remissão da doença após a tireoidectomia total ou quase total em indivíduos com CDT. Metodologia: foi realizada uma revisão sistemática da literatura na qual foram incluídos estudos controlados randomizados, não randomizados e observacionais, nos quais os pacientes estavam em pós-operatório de tireoidectomia total ou subtotal devido um dos CDT, e foram alocados a um dos dois grupos: PCI diagnóstica com 131I realizada antes da dose terapêutica com I131(intervenção), ou a PCI realizada com 123I antes da dose ablativa, ou não realização da PCI diagnóstica antes da dose terapêutica (ambos controle). O desfecho principal foi a remissão da doença avaliada pela taxa de sucesso ablativo em pelo menos seis meses de seguimento. Resultados: depois de realizadas as pesquisas nas bases eletrônicas Embase (1980–25/04/2017), Pubmed (1966–25/04/2017), CENTRAL (Registro de Ensaios Controlados da colaboração Cochrane) (25/04/2017) e Biblioteca Virtual da Saúde (1982–25/04/2017) foram identificadas 3005 referências. Dois revisores avaliaram independentemente os títulos e os resumos identificados pela pesquisa bibliográfica, e desses trabalhos, 23 eram potencialmente elegíveis, e por isso foram selecionados para leitura na íntegra. Foram incluídos 12 estudos, sendo quatro prospectivos e oito retrospectivos. Os primeiros envolveram 176 pacientes e os últimos 1241 indivíduos. Nos quatro estudos prospectivos, a taxa de sucesso ablativo em seis meses foi de 86% no grupo intervenção e 87% no controle, a metanálise não mostrou diferença significativa entre os grupos (RR 1,02; IC: 0.92,1.13, p= 0.66, I2=0%). Dentre os estudos observacionais, quatro estudos não apresentaram diferenças significativas entre os grupos, e em três o grupo controle teve uma taxa de sucesso ablativo significativamente maior. Conclusão: com uma qualidade da evidência baixa, dentre os estudos prospectivos não houve diferença significativa quanto a taxa de sucesso ablativo em pacientes que realizaram a PCI com 131I pré-dose ou a fizeram com 123I ou não fizeram essa PCI diagnóstica. Dentre os estudos observacionais, em três estudos os indivíduos que realizaram a PCI com 131I pré-dose tiveram uma redução significativa na taxa de sucesso ablativo em seis meses de seguimento, enquanto que em quatro estudos não houve diferença significativa entre os grupos.
Systematic Review of influence of whole body scanning with radionuclides of iodine previosly the 131I ablative treatment in patients with differentiated thyroid carcinoma
Keywords: câncer diferenciado de tireoide; pesquisa de corpo inteiro com 131I ou 123I; dose ablativa com 131I; Differentiated Thyroid Cancer; Whole Body Imaging with 131I or 123I; ablative dose with 131I